An Observational, Multicenter, Cohort Study Evaluating the Antiviral Efficacy and Safety in Korean Patients With Chronic Hepatitis B Receiving Pegylated Interferon-alpha 2a (Pegasys): TRACES Study. Issue 14 (April 2016) - Chon, Young Eun; Kim, Dong Joon; Kim, Sang Gyune; Kim, In Hee; Bae, Si Hyun; Hwang, Seong Gyu; Heo, Jeong; Jang, Jeong Won; Lee, Byung Seok; Kim, Hyung Joon; Jun, Dae Won; Kim, Kang Mo; et al.
Abstract : Abstract: Currently, limited data are available regarding the efficacy and safety of pegylated interferon alpha-2a (PEG-IFN α-2a) in Korean patients with chronic hepatitis B (CHB), in whom hepatitis B virus (HBV) genotype C is the most common type. We collected data from 439 patients (HBeAg positive, n = 349; HBeAg negative, n = 90) with CHB who were treated with PEG-IFN α-2a as a first-line therapy from 18 institutions. Treatment responses at the end of treatment (ET) and at 6 months posttreatment (PT6) were compared between the patients who were treated for 24 weeks versus 48 weeks, and adverse events (AEs) were evaluated. In HBeAg-positive patients, those who received PEG-IFN α-2a for 48 weeks showed significantly higher HBV DNA suppression (HBV DNA < 2000 IU/mL) than those who were treated for 24 weeks (48 weeks vs 24 weeks; at ET, 44.4% vs 36.7%, P = 0.035; at PT6, 35.9% vs 13.3%, P = 0.035). The HBeAg seroconversion rate at ET was 18.1% in 48-week treatment group, which is significantly higher than the 2.2% ( P < 0.001) that was seen in 24-week treatment group. This finding also continued at PT6 (29.0% vs 10.0%, P < 0.001). Following 48 weeks of treatment in HBeAg-negative patients, HBV DNA suppression at ET was higher than in HBeAg-positive patients (87.8% vs 44.4%). AEs were typical of those associated with PEG-IFN α-2a. In naïve Korean HBeAg-positive CHB patients treated with PEG-IFN α-2a, higher rates of HBV DNA suppression and HBeAg seroconversion were achieved in the 48-week treatment group than in the 24-week treatment group without additional risk of AEs.